2022
DOI: 10.1002/jhbp.1259
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of colectomy during pancreatoduodenectomy: An analysis of the pancreas‐targeted American College of Surgeons National Surgical Quality Improvement Program Registry

Abstract: Background Pancreatoduodenectomy is a complex operation with considerable morbidity and mortality. Locally advanced tumors may require concurrent colectomy. We hypothesized that a concurrent colectomy increases the risk associated with pancreatoduodenectomy. Methods This retrospective review of the 2014–2019 pancreas‐targeted American College of Surgeons National Surgical Quality Improvement Program registry classified operations as pancreatoduodenectomy (PD) versus pancreatoduodenectomy/colectomy (PD+C). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Other studies from single high-volume centers showed the association of colectomies with PD in 4.4 to 11.5% of patients [28][29][30]. A segmental or right colectomy is the most common type associated with PD [25][26][27].…”
Section: Indications For Pd With Concurrent Colectomiesmentioning
confidence: 92%
See 4 more Smart Citations
“…Other studies from single high-volume centers showed the association of colectomies with PD in 4.4 to 11.5% of patients [28][29][30]. A segmental or right colectomy is the most common type associated with PD [25][26][27].…”
Section: Indications For Pd With Concurrent Colectomiesmentioning
confidence: 92%
“…As mentioned above, the association of PD with colectomies is an uncommon surgical procedure in clinical practice. Studies including 3275 to 24,421 PDs each showed that a concurrent colectomy was required in only 1.4-2% of the patients [12,[25][26][27]. Other studies from single high-volume centers showed the association of colectomies with PD in 4.4 to 11.5% of patients [28][29][30].…”
Section: Indications For Pd With Concurrent Colectomiesmentioning
confidence: 99%
See 3 more Smart Citations